ESMO consensus guidelines for the management of patients with metastatic colorectal cancer - Van Cutsem, E (2016)
Colorectal cancer (CRC) is one of the most common malignancies in Western countries. Over the last 20 years, and the last decade in particular, the clinical outcome for patients with metastatic CRC (mCRC) has improved greatly due not only to an increase in the number of patients being referred for and undergoing surgical resection of their localised metastatic disease but also to a more strategic approach to the delivery of systemic therapy and an expansion in the use of ablative techniques. This reflects the increase in the number of patients that are being managed within a multidisciplinary team environment and specialist cancer centres, and the emergence over the same time period not only of improved imaging techniques but also prognostic and predictive molecular markers. Treatment decisions for patients with mCRC must be evidence-based. Thus, these ESMO consensus guidelines have been developed based on the current available evidence to provide a series of evidence-based recommendations to assist in the treatment and management of patients with mCRC in this rapidly evolving treatment setting.